A szervetlen-C és a szerves-C mennyiségének változása egy homoktalajban, meszezés hatására - Nagy, Péter Tamás; Filep, Tibor; Kincses, Sándorné (Acta Agraria Debreceniensis, 2002)
The effect of liming on different organic and inorganic carbon forms in soil was studied in a pot experiment on acidic sandy soil (pH(H2O)=4.38; pH(KCl)=3.42). We used three kinds of liming doses (which were signed M1, M2, M3,). M1 was half of the M2 dose; M2 was the calculated lime dose and M3 was one and the half dose of M2. Lime (CaCO3) was mixed into the soil in powdery form. In addition to liming treatments, a uniform N, P and K treatment (1-1-1g N, P2O5 and K2O per pot) was given. Water supply was set up to 75% field water capacity of soil. Pots were watered daily. During the vegetation period soil and plant (oats; Avena sativa L.) samples were taken from each treatment three times (after 6-10-15 weeks). We determined inorganic- and total-C of the soil by Vario EL element analyser (based on dry combustion method) and calculated the organic-C. The conclusions can be summarized as follows: – Liming treatments had a significant positive effect on the soil-pH and caused quantitative change of different carbon forms of soil. – Increasing tendency of liming doses caused more intensive changes in inorganic- and organic-C forms of soil. – A significant correlations was found between the soil pH and the inorganic-C fraction of soil. – A decreasing correlation was found between the vegetation period and the organic-C fraction.